2021
DOI: 10.20944/preprints202102.0466.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review on Response Mechanism of Plants to Drought Stress

Abstract: With the global climate anomalies and the destruction of ecological balance, water shortage has become a serious ecological problem facing all mankind, and drought has become a key factor restricting the development of agricultural production. Therefore, it is essential to study the drought tolerance of crops. On the basis of previous studies, we reviewed the effects of drought stress on plant morphology and physiology, including the changes of external morphology and internal structure of root, stem and leaf,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(5 citation statements)
references
References 181 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…Moreover, lipid-peroxidation and protein-degradation caused by salinity stress deteriorate the structural integrity of the membrane and increase the generation of ROS, which disrupt membrane fluidity and cause high electrolyte leakage ( Sachdev et al., 2021 ). In addition, abiotic stress like salinity alters the osmotic potential and water balance of plants, interfering with a number of exchange processes like transpiration (Tr) and stomatal conductance (Gs) ( Yang et al., 2021 ). Accordingly, the present study found a considerable decrease in CMSP, Pn, Gs, Tr, and chlorophyll under saline condition; however, the SHs (SH1-SH4) illustrated comparatively less decrease in these traits that is an indicator of their higher physiological tolerance ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lipid-peroxidation and protein-degradation caused by salinity stress deteriorate the structural integrity of the membrane and increase the generation of ROS, which disrupt membrane fluidity and cause high electrolyte leakage ( Sachdev et al., 2021 ). In addition, abiotic stress like salinity alters the osmotic potential and water balance of plants, interfering with a number of exchange processes like transpiration (Tr) and stomatal conductance (Gs) ( Yang et al., 2021 ). Accordingly, the present study found a considerable decrease in CMSP, Pn, Gs, Tr, and chlorophyll under saline condition; however, the SHs (SH1-SH4) illustrated comparatively less decrease in these traits that is an indicator of their higher physiological tolerance ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chlorophyll of content basil leaf (O. sanctum) was low at the young stage (22 SPAD unit) and achieved its highest content at the mature stage (35 SPAD unit) where the leaf colour was light green to mature leaf with the highest chlorophyll content with the dark green of coloration 19 . In addition, the thickness and drought condition of leaves affected the degradation of chlorophyll content after harvest, the thicker the leaves, the harder to be degraded 20 . These reasons may be the factor that affected the changes in brown colour in wet noodles treated with basil leaf extract.…”
Section: Discussionmentioning
confidence: 99%
“…(26) The functioning of the ribosome during stress is crucial for the timely synthesis of stress-responsive proteins. (27,28)Different stress and defense-related pathways get deactivated upon ribosomal impairment (29). This crosstalk between ribosome and stress-responsive protein serves as a novel approach to studying stress-tolerant plants.…”
Section: Endocytosismentioning
confidence: 99%